Predictors of adherence to screening guidelines for chronic diseases of lifestyle, cancers, and HIV in a health-insured population in South Africa - Adonis, L; Basu, D; Luiz, J; et al (My University, 2014)
BACKGROUND: Adherence to screening guidelines has been widely accepted to reduce morbidity, mortality, and cost outcomes. The aim of this study was to identify predictors of adherence to screening guidelines for chronic diseases of lifestyle (CDL), cancers, and HIV in a health-insured population in South Africa, some of whom voluntarily opt into a wellness program that incentivizes screening. METHOD: A cross-sectional study for the period 2007-2011 was conducted using a random sample of 170,471 health insurance members from a single insurer. Adherence to screening guidelines was calculated from medical claims data. RESULTS: Adherence to screening guidelines ranged from 1.1% for colorectal cancer to 40.9% for cholesterol screening. Members of the wellness program were up to three times more likely to screen for diseases (odds ratio [OR] = 3.2 for HIV screening, confidence interval [CI] = 2.75-3.73). Plan type (full comprehensive plan) was most strongly associated with cholesterol screening (OR = 3.53, CI = 3.27-3.80), and most negatively associated (hospital-only core plan) with cervical cancer screening (OR = 0.44, CI = 0.28-0.70). Gender was a negative predictor for glucose screening (OR = 0.88, CI = 0.82-0.96). Provincial residence was most strongly associated with cervical cancer screening (OR = 1.89, CI = 0.65-5.54). CONCLUSION: Adherence to screening recommendations was <50%. Plan type, gender, provincial residence, and belonging to an incentivized wellness program were associated with disproportionate utilization of screening services, even with equal payment access.
KIM
Keywords: HIV Infections; Chronic Disease; Early Detection of Cancer; Mass Screening; South Africa